Company Characteristics on the Corporate Social Reporting Index of Corporate Social and Environmental Disclosure in Indonesian Public Companies - Asrori, Asrori; Amal, Muhammad Ihlashul; Harjanto, Atta Putra (International Journal of Energy Economics and Policy, 2019)
Corporate Social and Environmental Disclosure (CSED) is a form of reporting on the implementation of social and environmental responsibilities that must be included in the company’s annual report. However, how extensive or how much information must be delivered is still voluntary. This paper attempts to examine the effect of earnings management, managerial ownership, profitability and firm size on corporate social and environment disclosure. The findings of this study reveal that earnings management, managerial ownership, company size and company profitability have a significant positive effect on the extent of corporate social responsibility and environmental disclosure. This finding encourages the government to stipulate regulations that explicitly and clearly regulate the practice and disclosure, and supervision of Corporate Social Responsibility (CSR) in companies in Indonesia so that the practice and disclosure of CSR in Indonesia is increasing. Keywords: Corporate Social Responsibility, Corporate Social and Environmental Disclosure, public companies, financial indicators. JEL Classification: E44, M14, Q56 DOI: https://doi.org/10.32479/ijeep.7990